Effect of planting geometry and chemical fertilizers on growth characteristics, essential oil yield and composition of Inula racemosa under cold desert conditions of western Himalayas - Sakshi Vishvamitera; Sidharth Baghla; Varun Parmar; Romika Thakur; Sanatsujat Singh; Sachin Vashisath; Dinesh Kumar; Satbeer Singh; Ramesh Chauhan (BMC Plant Biology)
Abstract Inula racemosa, a critically endangered medicinal plant of the western Himalayas, is known for its various industrial uses worldwide. Fertilizer application contributes to higher crop yield; however, their excessive use may lead to higher cost of cultivation and environmental pollution. Similarly, appropriate plant orientation significantly contributes to utilizing natural resources efficiently, leading to higher yields. Therefore, the study aimed to optimize the fertilizer dose for I. racemosa with a suitable planting geometry. A field experiment was carried out in the cold desert region of the western Himalayas comprising three planting geometries 30 × 30 cm (G1), 30 × 45 cm (G2) and 45 × 45 cm (G3) and four fertilizer doses (NPK) at the rates of 0 (F1), 90:60:30 kg ha−1 (F2), 120:75:40 kg ha−1 (F3), and 150:90:50 kg ha−1 (F4) from 2021 and 2022. The experiment was laid out in a split-plot design with 12 treatment combinations and replicated thrice. Planting geometry significantly affected all the parameters studied except the number of secondary roots and essential oil (EO) content. Planting geometry G2 recorded significantly higher values of all the morphological and yield traits; however, the lowest were observed in G1, except for plant height. Among fertilizer doses, F4 produced better results for all the growth and root yield components, whereas the control presented the lowest values. The highest fertilizer dose F4 resulted in dry root yield that were 6.34, 26.15 and 102.99% greater than those of F3, F2, and the control, respectively. The plants fertilized with NPK @ 150:90:50 kg ha−1 produced significantly highest EO yield, which was 125.40% greater than that of the control. The major EO constituents alantolactone, isoalantolactone, and β-elemene ranged from 59.44–63.65, 31.38–34.68 and 0.24–0.33%, respectively; however, their accumulation patterns were not consistent. Thus, a planting geometry of 30 × 45 cm in combination with NPK @ 150:90:50 kg ha−1 could improve the growth, dry root yield and EO yield of I. racemosa, which may encourage farmers in cold arid regions for cultivation and consequently aid in achieving its conservation, in addition to meeting ever-increasing industrial demand.  Graphical Abstract